Tachykinins and the hypothalamo–pituitary–gonadal axis: an update - Lasaga, Mercedes Isabel (2011)
Tachykinins play a critical role in neuroendocrine regulation of reproduction. The best known members of the family are substance P (SP), neurokinin A and neurokinin B. Tachykinins mediate their biological actions through three G protein-coupled receptors, named NK1, NK2, and NK3. SP was suggested to play an important role in the ovulatory process in mammals and humans. Recent findings suggest a role of tachykinins in the aging of the hypothalamo–pituitary–gonadal axis. A high presence of SP was found in the sheep pars tuberalis and evidence indicates that it may have some role in the control of prolactin secretion. The presence of SP was confirmed in Leydig cells of the rat testes of animals submitted to constant light or treated with estrogens. Tachykinins were found to increase the motility of human spermatozoa. Tachykinins were also found to be present in the mouse ovary and more specifically, in the granulose cells. It is possible that tachykinins may play an important role in the ovarian function. NKB has been implicated in the steroid feedback control of GnRH release. Human mutations in the gene encoding this peptide or its receptor (TACR3) lead to a defect in the control of GnRH. A specific subset of neurons in the arcuate nucleus of the hypothalamus, colocalized three neuropeptides, kisspeptin, NKB and dynorphin. This subpopulation of neurons mediates the gonadal hormone feedback control of GnRH secretion. NKB/NK3 signaling plays a role in puberty onset and fertility in humans. This minireview summarizes the recent data about the action of tachykinins on the hypothalamo–pituitary–gonadal axis.